Reconstitution of TGFBR2-mediated signaling causes upregulation of GDF-15 in HCT116 colorectal cancer cells - Lee, Jennifer; Fricke, Fabia; Kopitz, Jürgen; Gebert, Johannes (PLOS ONE, 2015)
Although inactivating frameshift mutations in the Transforming growth factor beta receptor type 2 (TGFBR2) gene are considered as drivers of microsatellite unstable (MSI) colorectal tumorigenesis, consequential alterations of the downstream target proteome are not resolved completely. Applying a click-it chemistry protein labeling approach combined with mass spectrometry in a MSI colorectal cancer model cell line, we identified 21 de novo synthesized proteins differentially expressed upon reconstituted TGFBR2 expression. One candidate gene, the TGF-ß family member Growth differentiation factor-15 (GDF-15), exhibited TGFBR2-dependent transcriptional upregulation causing increased intracellular and extracellular protein levels. As a new TGFBR2 target gene it may provide a link between the TGF-ß branch and the BMP/GDF branch of SMAD-mediated signaling.
Gesehen am 11.04.2015